On The Unsteady Aerodynamics Of Road Vehicles In The Dynamic Motions - Tsubokura, Makoto; Cheng, See Yuan; Okada, Yoshihiro; Nakashima, Takuji; Nouzawa, Takahide; Kobayashi, Toshiyuki (2012)
Unsteady aerodynamics of road vehicles in dy-namic pitching motion were investigated by numerical analysis. Dynamic coupling simulation of flow and vehicle motion was realized based on a large eddy simulation (LES) technique with moving boundary methods. Fully unstructured finite volume code previously developed was implemented for the road vehicle aerodynamics. Arbitrary Lagrangean-Eulerian (ALE) method was employed to handle vehicle’s ro-tating motion, particularly the dynamic pitching. This vehicle motion type is chosen because of the unsteady aerodynamics are expected to be crucial in regards to the comfort of passenger. By using the numerical simulation, a method to estimate the vehicle’s aerodynamic damping was proposed.